Analysis of the Effect of Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on the Profits of Go Public Banks in the Indonesia Stock Exchange (IDX) Period 2016 – 2021 - Sugeng Suroso (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
This study aims to determine the effect of the capital adequacy ratio (CAR) and loan to deposit ratio (LDR) on the profitability of banks that go public on the Indonesia Stock Exchange (IDX) for the period 2016 - 2021. The indicators used in this study are: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Return On Assets (ROA). One of the Profitability Ratios used as an indicator in this study is Return On Assets (ROA). ROA is a financial ratio to measure the ability of bank management in obtaining overall profit (profit). In this study, ROA is used as the dependent variable, while the Capital Adequacy Ratio and Loan to Deposit Ratio are independent variables. The two independent variables will be analyzed either partially or simultaneously to see whether or not there is an effect on ROA. The data used in this study is the ratio of CAR, LDR and ROA of publicly listed banks on the Indonesia Stock Exchange (IDX) for the period 2016 – 2021 with the number of banks listed and meeting the characteristics of 28 banks. In data analysis using classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, F test and T test. The results of the study using the F test together that CAR and LDR have an effect on ROA, while the T test shows that CAR has an effect on ROA and LDR has no effect on ROA.